Diagnostic Approaches to Invasive Candidiasis: Challenges and New Perspectives - Slepčanová, Hana; Dobiáš, Radim; Langer, Andrea Beatriz Sermeño; Káňová, Marcela; Hamal, Petr (Mycopathologia, 2025)
Invasive candidiasis is a serious infectious disease that affects 2-10% of patients in the intensive care unit. It is caused by fungi of the genus Candida, and its diagnosis relies on multiple complex laboratory methods. Blood culture remains the gold standard for yeast detection in the bloodstream but has limited clinical utility because of its low sensitivity and prolonged turnaround time. Newer diagnostic approaches, such as molecular methods for Candida spp. DNA detection, which enable faster identificationbut still entail limitations, including variability in sensitivity. Another valuable tool is the detection of (1,3)-β-D-glucan, a polysaccharide in yeast cell walls; however, this marker lacks specificity. Timely initiation of appropriate antifungal therapy is crucial because delayed treatment is associated with increased mortality. Preventive strategies, including strict hygiene protocols and antifungal stewardship programs, are vital to reducing the incidence of invasive candidiasis. Emerging research on siderophores as candidate biomarkers for fungal infections indicates promising diagnostic potential. Given the complex pathogenesis and diverse clinical manifestations of invasive candidiasis, multifaceted diagnostic and therapeutic approaches are required. A combination of novel biomarkers, rapid molecular diagnostics, and optimized treatment strategies is essential to improve patient outcomes and reduce the complications associated with this life-threatening infection.
Keywords: Biomarkers; lidé; diagnostické techniky molekulární; Candida; beta-glukany; Diagnostic Tests, Routine; Invasive candidiasis; T2Candida; Candidiasis, Invasive; Humans; kandidóza invazivní; β-D-glucan; diagnostické testy rutinní; biologické markery; Antifungal Agents; antifungální látky; beta-Glucans; Molecular diagnostics; Molecular Diagnostic Techniques